Cell-based immunotherapy in stage IIIA inflammatory breast cancer with declining innate immunity following successive chemotherapies: A case report - Chidambaram, Ranganathan; Terunuma, Hiroshi; Balamurugan, Madasamy; Dedeepiya, Vidyasagar Devaprasad; Sumana, Premkumar; Senthilkumar, Rajappa; Rajmohan, Mathaiyan; Karthick, Ramalingam; Preethy, Senthilkumar; Abraham, Samuel J.K (Molecular and clinical oncology, 2017)
Cancer stem cells in breast cancer migrating to the bone marrow may cause future metastasis, particularly during periods of decreased immunity. Natural killer (NK) cells have a role in immune surveillance and are able to target cancer stem cells. The present study reported a case in which NK cell-based autologous immune enhancement therapy was used combined with conventional treatments in a patient with stage IIIA breast cancer, yielding >28 months of disease-free survival. However, there was a gradual decline in the in vitro expansion of NK cells with subsequent chemotherapeutic treatments. As this NK cell decline following chemotherapy may contribute to cancer cell immune evasion and future metastasis; modifying current cancer therapies in order to avoid potentially compromising the immune system may lead to improved treatment outcomes.